Context Matters: Exploring the Mental Health Experience of Immigrant Muslim Women - Tirmazi M. Taqi; Takisha J. Carter; Soleman Abu-Bader; Nada Eltaiba; Huda A. Alhajjaj (Social Sciences, 2026)
The United States has long been a destination for immigrants seeking better economic opportunities and an improved quality of life, and among these populations, Muslim women represent a particularly vulnerable group facing unique challenges. First-generation Muslim immigrant women in America navigate a complex web of intersecting stressors that significantly impact their mental health and overall wellbeing. Despite the pervasiveness of mental health and heightened attention on mental health challenges post COVID-19, research on the mental health of the Muslim community—particularly immigrant Muslim women in the United States—is seldom studied. This qualitative study utilized a focus group among a purposive sample of immigrant Muslim women to explore the multifaceted mental health challenges with particular attention to how racism, Islamophobia, and acculturative stress create cumulative mental health burdens. Thematic analysis revealed five major themes highlighting the various mental health challenges faced by participants: experience encountering racism and discrimination, the importance of faith and Islamic practice in addressing mental health challenges, the role of family and peers in addressing mental health challenges, and mental health service utilization. These findings underscore the importance of culturally responsive mental health services and community-based interventions that recognize the intersection of migration, discrimination, and religious identity in shaping the mental health experiences of immigrant Muslim women.